Did Covid-19 change translation pedagogy? An assessment of the impacts of technological trends in shaping translation studies after the pandemic - Al-Awawdeh, Nabil; Al-Shaboul, Ibrahim Abdallah (Research Journal in Advanced Humanities, 2025)
Translation education has been massively impacted by the technological trends that emerged after the Covid-19 pandemic. In this study, the focus was to explore how changes in translation studies can be attributed to technological trends post-Covid. Data was gathered using online survey tool wherein 883 (including 674 undergraduates and 179 lecturers in translation studies) participated in the survey. The study tested five major hypotheses, exploring how technological integration post-Covid impact students; academic performance, how remote learning increased students’ engagement, the correlation between students’ access to technological tools and increase in learning outcomes, among other hypotheses. Analysis was conducted using regression analysis and other relevant statistical tools, including the CFA tool. The results affirmed that all the five hypotheses were accepted, indicating a strong positive correlation between technological integration and academic performance, remote learning and increased engagement, access to technology and increased learning outcome, and correlation between lecturers’ familiarity with technological tools and increase in teaching efficiency. The results further indicated that the virtual classroom was applied by 93.07% respondents during the pandemic; in contrast, only 9.06% of respondents indicated using this tool before the pandemic. Interestingly, post-pandemic, the use of virtual classrooms registered a slight decrease to 89.48%. For translation software, before the pandemic, only 29.76% of those surveyed indicated that they used software for translation, but this more than doubled to 66.96% during the pandemic. After the pandemic, the use of translation software was still at 87.38%. Collaborative platforms too got a good push during the pandemic with 52.93% of the respondents reported, whereas, only 21.47% of the respondents reported in pre-pandemic time. With the pandemic, the usage percentage of collaborative platforms went up to 89.05%. The automated evaluation tools experienced a significant growth from 37,65% prior to the pandemic to 75,37% during the pandemic, signifying the increased need for automation for grading and assessment. This increase can be attributed to the requirement of effective and multilevel evaluation methods in remote teaching. Surprisingly, after pandemic, the utilization of automated tools has jumped to 94.58%, indicating the prevalence of automated evaluation in translation education.